Pengaruh Strategi Segmenting, Targeting, Positioning dan Advertising Effectiveness terhadap Purchase Decision - Siti Salma Nurfadila; Suwarsi, Sri; Muhammad Taufik Permana, Rezi (UNISBA Press, 2024)
Abstract. This research aims to find out how segmenting, targeting, positioning, advertising effectiveness and purchase decision strategies are described, as well as to find out the influence of segmenting, targeting, positioning and advertising effectiveness strategies on purchase decisions for Emina Skincare products on the Tiktok application. The factors tested in this research are segmenting, targeting, positioning, and advertising effectiveness as independent variables, while purchase decision is the dependent variable. The research method used in this research is descriptive and verification methods. The sampling technique used in this research is a non-probability sampling technique with a purposive sampling method, using the Cochran formula so that the sample in the study was 96 consumers of Emina Skincare products on the Tiktok application. The analytical method used in this research is multiple linear regression analysis. Partial and simultaneous research results show that segmenting, targeting, positioning and advertising effectiveness have a significant effect on purchase decisions for Emina Skincare products on the Tiktok application. Keywords: Segmenting, Targeting, Positioning, Advertising Effectiveness, and Purchase Decision Abstrak. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran strategi segmenting, targeting, positioning, advertising effectiveness, dan purchase decision, serta untuk mengetahui pengaruh strategi segmenting, targeting, positioning, dan advertising effectiveness terhadap purchase decision pada produk Skincare Emina di Aplikasi Tiktok. Faktor-faktor yang diuji dalam penelitian ini adalah segmenting, targeting, positioning, dan advertising effectiveness sebagai variabel independen, sedangkan purchase decision sebagai variabel dependen. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif dan verifikatif. Teknik penentuan sampel yang digunakan dalam penelitian ini yaitu teknik non probability sampling dengan metode purposive sampling, dengan menggunakan rumus Cochran sehingga sampel dalam penelitian sebanyak 96 konsumen produk Skincare Emina di Aplikasi Tiktok. Metode analisis yang digunakan dalam penelitian ini adalah analisis regresi linear berganda. Hasil penelitian secara parsial dan simultan menunjukan bahwa segmenting, targeting, positioning, dan advertising effectiveness berpengaruh signifikan terhadap purchase decision pada produk Skincare Emina di Aplikasi Tiktok. Kata Kunci: Segmenting, Targeting, Positioning, Advertising Effectiveness, dan Purchase Decision.